2017
DOI: 10.1038/s41598-017-06631-z
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex genes partly explain early survival in house sparrows

Abstract: Environmental factors and genetic incompatibilities between parents have been suggested as important determinants for embryonic mortality and survival. The genetic set-up of the immune system, specifically the highly polymorphic major histocompatibility complex (MHC) may also influence individual resistance to infections. MHC proteins are important for an appropriate adaptive immune response and enable T-cells to separate ‘self’ from ‘non-self’. Here we investigate the importance of MHC functional diversity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 68 publications
2
19
0
1
Order By: Relevance
“…Second, some studies have reported associations between fitness and specific MHC alleles or supertypes (clusters of MHC alleles with similar physicochemical properties at their antigen-binding sites). For example, Lukasch et al (24) found that a specific MHC allele was associated with higher survival of house sparrow fledglings ( Passer domesticus ). Another study of great tits ( Parus major ) using mark-recapture data identified three MHC supertypes associated with fitness components, one with increased survival, one with increased lifetime reproductive success and another one with decreased lifetime reproductive success (25).…”
Section: Introductionmentioning
confidence: 99%
“…Second, some studies have reported associations between fitness and specific MHC alleles or supertypes (clusters of MHC alleles with similar physicochemical properties at their antigen-binding sites). For example, Lukasch et al (24) found that a specific MHC allele was associated with higher survival of house sparrow fledglings ( Passer domesticus ). Another study of great tits ( Parus major ) using mark-recapture data identified three MHC supertypes associated with fitness components, one with increased survival, one with increased lifetime reproductive success and another one with decreased lifetime reproductive success (25).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the observation that males possessing an allele that may impair survival have songs that can be characterized by wider frequency ranges suggests that it may be beneficial for females to prefer males that sing at narrower bandwidths. Such males are unlikely to carry an MHC allele that makes individuals susceptible to parasitism and to have a genetic profile that incurs survival costs (see, e.g., Kloch, Baran, Buczek, Konarzewski, & Radwan, 2013;Loiseau et al, 2011;Lukasch et al, 2017). Singing at narrower frequency ranges may be more efficient in densely vegetated habitats, as it makes the signal less degradable or it allows the energy concentrated over small frequency bands for higher propagation (Boncoraglio & Saino, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The third, biologically motivated interpretation relied on the fitness value of MHC alleles, which was estimated relying on the strength of association between the presence of allele and longevity. If a particular allele implies parasite resistance (or susceptibility), individuals that harbour these alleles should realize higher (or lower) survival and live longer than individuals that do not have the allele (e.g., Bateson et al., ; Brouwer et al., ; Lukasch et al., ; Paterson, Wilson, & Pemberton, ; Sepil, Lachish, & Sheldon, ). Correspondingly, we tested for the association of each allele with lifespan (estimated as the oldest age in our long‐term ringing records) in a t test, from which the derived statistic was converted into an effect size ( r ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Lukasch et al. ), the role of gamete or early life viability in reducing mutation load has received limited attention (Agrawal and Whitlock ; Plough et al. ; Alavioon et al.…”
mentioning
confidence: 99%